Nanosized GdVO4 powders synthesized by sol–gel method using different carboxylic acids - Kaowphong S. (2017)
© 2016 The Nonferrous Metals Society of China and Springer-Verlag Berlin Heidelberg Nanosized GdVO 4 powders were synthesized via a sol–gel method using different carboxylic acids as chelating agent, followed by calcination at 600 °C for 3 h. The effect of different carboxylic acids such as citric acid, malic acid, and tartaric acid on the characteristics of the nanosized GdVO 4 powders was investigated. The GdVO 4 powder was also synthesized without carboxylic acid for comparison. The thermal decomposition process of the carboxylate precursors was investigated by thermogravimetric differential thermal analysis (TG-DTA). X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscope (FESEM), transmission electron microscope (TEM), and surface area measurement data were used to confirm the formation of nanocrystalline GdVO 4 powders. It is found that the synthesis using the carboxylic acid with higher heat of combustion results in the powder with larger crystallite size. The difference in the steric effect of the acids used, which was evaluated by a computational method, also affects the degree of agglomeration of the synthesized powders.